Narratives on the Chilean Social Outbreak - Castillo Salazar, Daniel (2026)
This article studies the narratives about the Chilean social outbreak produced by the social sciences. It is based on a systematic review of scientific articles and academic books published between 2019 and 2025, identifying what they reveal about the reasons that led people to mobilize, and to legitimize or delegitimize the status quo in that context. It concludes that narratives about the social outbreak tend to suggest that people mobilized due to the emotions and sensations they experienced; that the legitimization of the status quo is mainly related to the ideology constructed by the dominant sectors; and that its illegitimacy stems from a negative assessment of the system and its institutions. These findings offer insights into reinterpreting the social outbreak in retrospect, highlighting the scientific knowledge produced about this phenomenon.